Nano-Engineering of New Photoreactive Materials Having Fluorine Units: Synthesis and Photoalignment of Liquid Crystals - M. M., Yusoff; Rasha, Ata Alaa; Hegde, Gurumurthy; Arun, M Isloor; Boodappa, Chandrakantha; Shridhar, Mallad; Lachezar, Komitov (Scientific Research Publishing Inc, 2013)
In order to investigate the photoalignment mechanism of nematic liquid crystals on an oxadiazoles, new 1,3,4-oxadiazole having fluorine atoms as terminal, as well as sideways was synthesized. Linearly polarized UV light shined in these nano-layered films causes the preferential direction of the liquid crystal molecules either perpendicular (in the case of terminal fluoro substitution) or parallel (in the case of sideways fluorine substitution) to the polarized direction. A powerful indication about the relationship between molecular structure and alignment properties where just by changing fluorine atom can change the entire alignment direction is proposed. Such information is indispensable for the design and synthesis of photoalignment materials for liquid crystal displays of high quality.